Chrysostom’s “Apatheia of the Angels” - Miller, Samantha L. (Journal of early Christian history, 2025)
John Chrysostom uses a curious phrase to describe Adam and Eve’s fall in his homilies on Genesis: they lost the “apatheia of the angels” (tōn angelōn tēn apatheian). This suggests that Chrysostom believed that Adam and Eve possessed apatheia before the fall, even in their bodies. He uses the phrase again when writing to Olympias, encouraging the widow to imitate “the apatheia of the angels” as the way to virtue. And again he tells his congregants that monks are an example to them of how to live, as they “imitate the apatheia of the incorporeal powers.” Chrysostom’s understanding of anthropology relies at least in part on his understanding of both angels and ascetism. I argue that Chrysostom thinks that lay Christians have the same potential as monks to become like angels. When Chrysostom tells his congregants to imitate the monks, it is not so they can become like the monks but so that they can become angelic. The “apatheia of the angels” is the blueprint for human life, what humans were made for, and what they aim to be restored to even as they live in the present on earth. Apatheia is a key aspect of Chrysostom’s anthropology.